Ecocritical Analysis of Tte Marine Ecosystem in the "Documentary: Seaspiracy (2021)” Movie by Ali Tabrizi - Damaliya, Windy; Priyoto, Priyoto; Marleni, Sri (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
The writer thinks to make the above topic as a matter that must be researched further because the writer sees something that can be used as material for analysis and can be an additional scientific value for knowledge and new learning in this literary science. The problem discussed in this research is what kind of ecocriticism is presented in the film "Documentary: Seaspiracy (2021)" by Ali Tabrizi? In this study the writer wants to provide ecocriticism of marine ecosystems with the title "ecocritical analysis of marine ecosystems" this research discusses literary ecocriticism, namely the relationship between nature and humans which focuses on the film "documentary: Seaspiracy". The method used in this research is descriptive qualitative, which describes the results of the research verbally. The writer also uses an ecological approach to focus and present the findings. The results of this study show that there are many criticisms that this movie wants to convey, and the images presented have many specific criticisms to show ecological damage, especially in the marine area. In this film, the author also uses Greg Garrard's theory of ecocriticism to clarify and dig deeper into the attitude of environmental criticism by the players in the form of images and conversations conveyed in through the "Documentary: Seaspiracy (2021)" movie.